Asset Protection through Prenuptial Agreements: A Family Law Perspective in the Modern Era - Indira, Anne Graciela; Meylina, Dinaomi Romauli (Jurnal Indonesia Sosial Sains, 2025)
Amid the dynamics of modern social and economic life, marital agreements have become increasingly relevant, especially for young couples who begin building their careers and assets at an early stage. This study aims to examine the urgency of marital agreements from the perspective of Indonesian positive law and to analyze the prevailing social responses within society. Using a juridical-sociological approach, the research reviews the provisions in the Indonesian Civil Code, the Marriage Law, and the Constitutional Court Decision No. 69/PUU-XIII/2015, which allows for postnuptial agreements. Additionally, it explores young couples’ perceptions of this issue through literature review and secondary data analysis. The findings reveal that although marital agreements provide legal certainty and asset protection, many young couples are reluctant to pursue them due to negative societal stigma. Therefore, educational efforts and cultural legal reforms are needed to reframe prenuptial agreements as a preventive and rational legal measure, rather than a threat to marital harmony. This study contributes to promoting a more progressive and inclusive legal understanding among the younger generation.